2016
DOI: 10.1049/iet-nbt.2015.0061
|View full text |Cite
|
Sign up to set email alerts
|

Study of bio‐fabrication of iron nanoparticles and their fungicidal property against phytopathogens of apple orchards

Abstract: Current research trends on iron nanoparticles (FeNPs) are extensively focused because of their unique magnetic and electrical properties mostly applicable in essential medical devices. However, their fungicidal property against plant pathogens is very less known until date. Present study demonstrates a green technique for blending of FeNPs by utilising aqueous extract of neem leaf ( A Juss.) as reducing agent. Various characterisation techniques such as ultraviolet (UV)-visible spectroscopy, Fourier transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…During synthesis of iron nanoparticles the reduction of Fe 2+ or Fe 3+ ions to Fe 0 is confirmed by visible color change to brown/black depending of nanoparticles concentration in the reaction mixture. Color change indicated the formation of FeNPs physically (Mohamed et al, 2015;Devatha et al, 2016;Ahmad et al, 2017;Asghar et al, 2018;Fahmy et al, 2018). For the four extracellular filtrates used in this study a brown color was revealed in all samples at the end of the assay, but confirmation of FeNPs was carry out by UV-visible spectrophotometer and analysis TEM.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…During synthesis of iron nanoparticles the reduction of Fe 2+ or Fe 3+ ions to Fe 0 is confirmed by visible color change to brown/black depending of nanoparticles concentration in the reaction mixture. Color change indicated the formation of FeNPs physically (Mohamed et al, 2015;Devatha et al, 2016;Ahmad et al, 2017;Asghar et al, 2018;Fahmy et al, 2018). For the four extracellular filtrates used in this study a brown color was revealed in all samples at the end of the assay, but confirmation of FeNPs was carry out by UV-visible spectrophotometer and analysis TEM.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, the spectrum band of EF-PDB was narrower than that of EF-C, indicating that possibly the size dispersion of the nanoparticles biosynthesized in the EF-PDB was low comparing with EF-C. Mohemed et al (2015) reported that FePNs biosynthesized by biomass of A. alternata had a cubic shape, with average particle diameter of 9 ± 3 nm, the culture medium and production conditions was different to those used in this research. Another sizes and shape of FeNPs has been reported as 20-80 nm (Ahmad et al, 2017), amorphous and spherical of 40 to 70 nm (Yi et al, 2019), spherical of 5-10 nm (Murgueitio et al, 2018), spherical of 96-110 nm (Devatha et al, 2018), spherical of 50 to 60 nm (Fahmy et al, 2018), spherical of 42-60 nm (Asghar et al, 2018). To MH-FeNPs and CCP-FeNPs, sizes of 84.81 and 48.91 nm was detected respectively.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations